Effects of a health education intervention on insecticide treated nets use and its practices among pregnant women attending antenatal clinic in Royal hospital, Enugu State, Nigeria: a Pilot study - Onyinyechi, Opara Monica; Ismail, Suriani; Nashriq, Ahmad Iqmer (AMJ, 2023)
Malaria remains the most prevalent parasite infection accountable for the high burden of disease and deaths in low-income countries. Approximately half of the global population lives in malaria-endemic areas, pregnant women and young children below the age of 5-years are considered as high-risk group for the transmission of malaria. A pilot study was conducted in Royal hospital, Enugu State, Nigeria. The health education intervention contents were prepared initially and pre-tested by piloting 30 pregnant women. The pre-test was done two times, with an interval of 10 days in order to evaluate the accuracy of the original findings with a retest. A total of 30 pregnant women participated in the study Majority of the pregnant women belong to Igbo ethic group 27(90). All the pregnant women live in the city 30(100). The result of this study reported that a total of 29 respondents had good knowledge of malaria prevention practice. Results proved that health education could be an effective if it is included in routine sessions provided to pregnant women in order to encourage them to practice the use of ITN. This could not only be beneficial in preventing malaria and reducing its burden of disease, it can also improve maternal morbidity and mortality among pregnant women.